Gymnothorax melanosomatus, a new moray eel (Teleostei: Anguilliformes: Muraenidae) from southeastern Taiwan - Loh, Kar-Hoe; Shao, Kwang-Tsao; Chen, Hong-Ming (2011)
Gymnothorax melanosomatus new species, is described here on the basis of eight specimens collected from eastern coastal Taiwan at a depth 50-180 m. This new moray eel is distinguished from a closely similar species, G. prolatus, by a combination of the following characters: a uniformly black body when fresh (vs. brown), a relatively long preanal length 58.5 % of TL (vs. 48.9), shorter snout length 17.8 % of HL (vs. 20.0), interobital width 12.2 % of HL (vs. 14.3); more preanal vertebrae 105-109 (vs. 74-86) and total vertebrae 201-211 (vs. 174-190). The male and female are not different in body color and pattern, but the numbers of median intermaxillary teeth are different between the sexes, 0 in male and 2-3 in female. Key words: